Evaluation of antioxidant and antiproliferative activities of 1,2-bis (p-amino-phenoxy) ethane derivative Schiff bases and metal complexes - Parlak, Akif Evren; Cakmak, Haluk; Sandal, Suleyman; Yilmaz, Bayram; Sekerci, Memet; Genc, Zuhal Karagoz; Karatepe, Mustafa (Wiley, 2019)
In this study, the effects of the two Schiff base derivatives and their metal complexes were tested for MDA concentration, which is an indicator of lipid peroxidation, antioxidant vitamin A, vitamin E, and vitamin C levels in cell culture. A comparison was performed among the groups and it was observed that MDA, vitamin A, vitamin E, and vitamin C concentrations were statistically changed. According to the results, all compounds caused a significant oxidative stress without Zn complexes. Moreover, Mn(II), Cu(II), Zn(II), and Ni(II) complexes of Schiff bases derived from a condensation of 1,2-bis (p-aminophenoxy) ethane with naphthaldehydes and 4-methoxy benzaldehyde were examined in terms of antitumor activity against MCF-7 human breast cancer and L1210 murine leukemia cells. Furthermore, the derivatives were tested for antioxidative and prooxidative effects on MCF-7 breast cancer cells. The compounds which were tested revealed that there was an antitumor activity for MCF-7 and L 1210 cancer cells. Also, some of the compounds induced oxidative harmful.
Keywords: aminophenoxy; antioxidant activity; cancer; cytotoxicity; Schiff base